Il fantasma del traduttore nella stampa cinese: alcune riflessioni sulla traduzione istituzionale (Altre Modernità, 2018)
Institutional translation is a well established practice in the Chinese press. Although lacking in individual visibility, translators in these contexts are key mediators for the creation of an authoritative information flow at the global level. Through a corpus of journalistic texts published in 2017 by Renmin ribao online in three different languages (Chinese, French and English), this paper focuses on the interaction between the mechanism of recontextualisation of a political event in news production and the practice of translation. The aim is to discuss the effectiveness of the products of institutional translation in promoting a positive image of the country and in strengthening the legitimacy of Chinese national political institutions worldwide.